The rise and organisation of the Achaemenid Empire : the eastern Iranian evidence / by W.J. Vogelsang. - Vogelsang, W. J. (Studies in the history of the ancient Near East, 1992)
"The present book discusses the eastern part of the Persian Achaemenid Empire, which was founded around the middle of the sixth century B C by Cyrus the Great. Within twenty years the empire stretched from the Aegaean coast in the west, to the Kabul valley in the east. How did the Persians manage to conquer such a vast area within such a short time? And how did they manage to preserve their empire for two hundred years before being defeated by the military genius of Alexander of Macedon?" "The answer to the above questions is sought in the chaotic years that preceded the rise of the Achaemenids. On the basis of geographical and general historical information, the Persian Achaemenid texts and reliefs, classical sources and archaeological material, this study draws attention to the nomads from the Central Asian steppes and deserts who throughout history have played a major role in the developments that took place on the Iranian Plateau and beyond."--BOOK JACKET.